Transparency and Public Access to Electronic Civil Case Documents: Between Openness and Data Privacy - Ardelia, Sekar Galuh; Wiraguna, Sidi Ahyar (Media Hukum Indonesia (MHI), 2026)
The implementation of the electronic court system in Indonesia has brought numerous benefits, such as increased transparency and accountability of the judiciary. However, this system also poses challenges regarding the protection of personal data contained in case documents. Public information openness must be balanced with strict regulations to protect the privacy of individuals involved in legal proceedings. This research analyzes the challenges and policy recommendations aimed at strengthening the balance between transparency and personal data protection in the electronic court system. The recommendations include the development of derivative regulations for the PDP Law, the implementation of secure document management systems, and training for court officials and the public regarding information access rights. This study also suggests further research on the impact of transparency on public trust and international comparative studies to improve the implementation of the electronic court system in Indonesia